Preferences of support and barriers and facilitators to help-seeking in pregnant women with severe fear of childbirth in Sweden: a mixed-method study - Carita Nordin-Remberger; Michael B. Wells; Joanne Woodford; Karin S. Lindelöf; Margareta Johansson (BMC, 2024)
Abstract Background There are few support interventions for women with fear of childbirth tailored towards type of fears and parity. To inform the future development of an acceptable and relevant intervention for women with severe fear of childbirth, primary objectives were to examine: (1) pregnant women's experiences of and preferences for support and (2) barriers and facilitators to help-seeking. Secondary objectives were to examine if there are any differences based on pregnant women's parity. Methods Pregnant women with a severe fear of childbirth in Sweden completed an online cross-sectional survey between February and September 2022. Severe fear of childbirth was measured using the fear of childbirth scale. Quantitative data were analysed using descriptive and inferential statistics and free answers were analysed using manifest content analysis. A contiguous approach to integration was adopted with qualitative and quantitative findings reported separately. Results In total, 609 participants, 364 nulliparous and 245 parous women, had severe fear of childbirth. The main category "A twisting road to walk towards receiving support for fear of childbirth" was explored and described by the generic categories: Longing for support, Struggling to ask for support, and Facilitating aspects of seeking support. Over half (63.5%), of pregnant women without planned or ongoing treatment, wanted support for fear of childbirth. Most (60.2%) pregnant women with ongoing or completed fear of childbirth treatment regarded the treatment as less helpful or not at all helpful. If fear of childbirth treatment was not planned, 35.8% of women would have liked to have received treatment. Barriers to help seeking included stigma surrounding fear of childbirth, previous negative experiences with healthcare contacts, fear of not being believed, fear of not being listened to, and discomfort of having to face their fears. Facilitators to help seeking included receiving respectful professional support that was easily available, flexible, and close to home. Conclusions Most pregnant women with severe fear of childbirth felt unsupported during pregnancy. Findings emphasise the need to develop individual and easily accessible psychological support for women with severe fear of childbirth, delivered by trained professionals with an empathetic and respectful attitude.